PESAN SOSIAL DAN BENTUK PESAN PADA KOMIK “HAI,MIIKO!” (STUDI ANALISIS ISI) - Cicy Amelia; Evawani Elysa Lubis (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
circulating in Indonesia is dominated by Japanese comics (manga) and translated and repackaged in Indonesia. The power of comics is in words and pictures. The comic "Hi, Miiko!" is one of the most popular comics in Indonesia that tells the daily social life of children. The content of social reality that becomes a social message will be a variable in this research namely social values, social deviations, and social control. Each variable will be put into 2 categories, according to the power of the comic (words & picture) and the message form (verbal & nonverbal). There are two categories of social messages that are told (written words) and social message categories that are showed (picture). The theory used in this research is Paul Ricoeur's theory of manuscripts / messages. The purpose of this research is to know how to describe the characteristic of social message and form of message on comic "Hi, Miiko!" With identification problem how big percentage of social message content and message form each variable per category.This research uses descriptive quantitative descriptive research method, with data accumulation technique is coding sheet that given to 2 coder, with 140 scene sample or 28 theme through stratified random sampling technique. Data analysis techniques in this study is descriptive statistical techniques by using frequency tables and percentages.The results of this study indicate that the message of social values as much as 73.58% for the written words category and 60.8% for the picture category. Then social deviation messages in sub-variables, form deviations of 32.5% for written words and 24.7% for pictures, sub-variable types of deviant behavior as much as 37.9% for written words and 30% for pictures. Lastly, for messages of social control each of 27.2% for written words and also picture category. This shows that the greatest social message content in the comic "Hi, Miiko!" is the message of its social values.Keyword : Comic, Form of Communication, Social Messages, Written Words, Picture